Remote sensing of atmosphere and ocean from space : models, instruments and techniques - International Summer School on Atmospheric and Oceanic Sciences (1st : 2000 : L'Aquila, Italy); Marzano, Frank S.; Visconti, Guido, 1943- (Dordrecht, The Netherlands : Kluwer Academic Pubs, 2002)
40